Penurunan Konsumsi Steam Di PG Modjo-Sragen dengan Konsep Heat- Process Integration Menggunakan Energy Utilization Diagram - Arief Budiman (Seminar Nasional Teknik Kimia Kejuangan, 2015)
Sugar factories can meet its own energy consumption, without using other fuels except bagasse, if consumption Steam on Cane (SOC) can reach 40-50% by weight of cane. Sugar factory can do cogeneration and generate electricity which can be sold to the grid if the consumption steam on cane reached a maximum of 40% by weight of sugar cane.This study aims to reduce the consumption of SOC in the process house using innovation of process configuration. EUD (Energy Utilization Diagram) is a thermodynamic analysis based on the concept exergy. EUD is used to evaluate the configuration process in order to obtain a better configuration of the existing configuration. The study obtained a configuration process with SOC <40%. Evaporation system used a quintuple effect. Vapor # 4 is used for energy donor heater # 1, Vapor # 3 used donor of energy to the heater # 2 and vacuum pan. Vapor # 1 is used for energy donor heater # 3. Exhaust steam pressure of 0.8-1 kg / cm2 is only used in the evaporator # 1.